The Effect of Social Media on Cumulative Abnormal Returns for Publicly Listed Corporations - Arellano, Cindy (2014)
The investigation’s main objective is to examine the relationship between linguistic tone in Twitter messages posted by corporations and financial analysts, and abnormal stock returns.